Intrahepatic Pseudoaneurysm of Right Hepatic Artery after Gunshot Thoracic-Abdominal Injury. A Case Report and Review of the Literature - Dogjani, Agron; Haxhirexha, Kastriot; Gjata, Arben; Dhima, Arben; Blloshmi, Amarildo (Archives of Clinical and Medical Case Reports, 2022)
Pseudo aneurysms of the right hepatic artery are uncommon, appearing in approximately 1% of hepatic trauma cases, and most are extrahepatic (80%) and have a late-onset [1]. Although they are usually asymptomatic, they should always be treated because of the high risk of complications, especially breakage. We present a case of post-traumatic hepatic artery pseudoaneurysm that was successfully treated using this open surgical technique. Intrahepatic pseudoaneurysm (IHPA) following shotgun injury is rarely reported. Timely diagnosis is crucial. We advise keeping in mind the possibility of IHPA, when dealing with high-grade liver injury. CT is recommended before removal of perihepatic packs, as it may pick up a lifethreatening pseudoaneurysm. For the treatment of visceral pseudo aneurysms, it is necessary to know all therapeutic options and to evaluate the convenience of each one. In the absence of sophisticated imaging and intra-arterial embolization, we contribute by adding our experience to the case reported in the bibliography. In conclusion, this study shows that IHPA develops in patients after traumatic liver injury. To avoid potentially life-threatening hemorrhages from a hepatic pseudoaneurysm after trauma, it seems appropriate to now manage all surgical techniques in the absence of angioembolization service.